Antidepressant drugs and teenage suicide in Hungary: Time trend and seasonality analysis. (August 2015) - Otuyelu1, Ekundayo; Foldvari, Anett; Szabo, Edit; Sipos, Valeria; Edafiogho, Peter; Szucs, Maria; Dome, Peter; Rihmer, Zoltan; Sandor, Janos
Abstract Objective. The aim of the present study was to analyze the relationship between increasing utilization of antidepressants and lithium, and suicide rate of persons less than 20 years of age in Hungary, with particular regard to seasonal patterns. Methods. Time trend analysis was carried out to determine the correlation between antidepressant and lithium prescription patterns in Hungarian persons under age of 20 years as well as seasonal variations within the study period from January 1998 to December 2006. Results. There was a significant correlation (P = 0.03) between the eight-fold increase in antidepressant + lithium prescriptions and decreasing suicides in young Hungarian people under 20 years of age within the study period. Lithium, selective serotonin reuptake inhibitors (SSRIs) and the group of "other antidepressant drugs" rather than nonselective monoamine reuptake inhibitors and monoamine oxidase-A inhibitors were responsible for this association. No significant association could be drawn from seasonal variation with boys (P = 0.964), girls (P = 0.140), or both genders (P = 0.997). Limitation. Ecological study design. Conclusion. Our findings are in good agreement with large-scale ecological studies showing that the beneficial effect of more widely used antidepressants at a given point could appear on the level of suicide rate of the general population even among patients under the age of 20 years.